2018
DOI: 10.1182/blood-2018-05-851360
|View full text |Cite
|
Sign up to set email alerts
|

RH genotype matching for transfusion support in sickle cell disease

Abstract: Rh alloimmunization remains a challenge for patients with sickle cell disease (SCD) despite transfusion of serologic Rh C, E, and K antigen-matched red cells. Inheritance of altered alleles contributes to the prevalence of Rh antibodies after blood transfusion in patients with SCD and explains approximately one-third of cases. The remainder seem to be stimulated by altered Rh proteins on African American donor red cells. Matching patients with donors on the basis of genotype may mitigate Rh alloimmunization, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
125
4
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(138 citation statements)
references
References 19 publications
6
125
4
3
Order By: Relevance
“…Chou et al [46], recently found that the RH allele frequencies between patients with SCD and African American donors are similar. Besides, SCD patients and African American donors studied by Chou et al inherit more altered RHD and RHCE alleles than SCD patients and donors included in our study.…”
Section: Discussionmentioning
confidence: 94%
“…Chou et al [46], recently found that the RH allele frequencies between patients with SCD and African American donors are similar. Besides, SCD patients and African American donors studied by Chou et al inherit more altered RHD and RHCE alleles than SCD patients and donors included in our study.…”
Section: Discussionmentioning
confidence: 94%
“…Persons with the same race and ethnicity are more likely to have the same major and minor blood antigens and transfusing blood to recipients from donors with the same race and ethnicity can reduce the risk of complications related to mismatched antigens . For example, persons with sickle cell disease can require frequent transfusions and are at a high risk of developing alloantibodies; recruiting donors from racially diverse populations for blood antigen matching can reduce the risk of alloimmunization . New thresholds which have increased the minimum Hgb for male donors may have resulted in more deferrals of black males compared to other races, likely because healthy black males have been reported to have lower Hgb level than white males .…”
Section: Discussionmentioning
confidence: 99%
“…37 For example, persons with sickle cell disease can require frequent transfusions and are at a high risk of developing alloantibodies; recruiting donors from racially diverse populations for blood antigen matching can reduce the risk of alloimmunization. [38][39][40] New thresholds which have increased the minimum Hgb for male donors may have resulted in more deferrals of black males compared to other races, likely because healthy black males have been reported to have lower Hgb level than white males. 25,35,41 Strategic planning tools to increase African-American blood donation are available, 37 but additional studies to determine effective methods to increase donations among minorities are needed.…”
Section: Donorsmentioning
confidence: 99%
“…While it is proposed that improved RH allele matching would decrease this rate of alloimmunisation in SCD patients, this raises the question as to whether matching is possible with current blood donor demographics, given that these RH alleles are not prevalent amongst European donors. Chou et al () showed first that RH allele frequencies between SCD patients ( n = 857) and African American donors ( n = 587) were similar. They then applied statistical modelling to estimate the donor recruitment that would be required to provide additional ‘prophylactic RH genetic matching’ (along with Rh and Kell serology matching).…”
Section: Wes For Sickle Cell Patients and Feasibility For Matching Wimentioning
confidence: 98%